Lombardo's reagent - Chand, Hemender R. (Synlett, 2009)

Efficient synthesis of 1,5-benzodiazepines catalyzed by bismuth nitrate - Bhattacharya, Asish K.; Dange, Santoshkumar S.; Polanki, Innaiah K.; Chand, Hemender R. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2014)
An efficient method has been developed for the synthesis of biologically active 1,5-benzodiazepines in one-pot by reacting o-phenylenediamine and ketones catalyzed by bismuth nitrate pentahydrate at room temperature or under microwave irradiation.
Keywords: 1; 5-benzodiazepines; bismuth nitrate pentahydrate; o-Phenylenediamine; synthetic methods

Clerodane type diterpene as a novel antifungal agent from polyalthia longifolia var. pendula - Bhattacharya, Asish K.; Chand, Hemender R.; John, Jyothis; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2015)
Bioactivity-guided chemical examination of methanolic extract of leaves of Polyalthia longifolia var. pendula led to the isolation of the active constituent, a diterpene 1 which was identified as 16α-hydroxycleroda-3,13(14)Z-dien-15,16-olide on the basis of its spectral data. Among the tested strains, diterpene 1 was found to exhibit antifungal activities having MIC90 values of 50.3, 100.6 and 201.2 μM against Candida albicans NCIM3557, Cryptococcus neoformans NCIM3542 (human pathogens) and Neurospora crassa NCIM870 (saprophyte), respectively. Initial, structure–activity-relationship (SAR) data generated by synthesizing some derivatives revealed that the double bond between C3–C4 and the free hydroxyl group at C16 are crucial for the antifungal activity of the diterpene 1. The mode of action of 1 in C. albicans is due to compromised cell membrane permeability and also probably due to disruption of cell wall structures. The red blood cell haemolysis of all the compounds (1–4) did not show any significant haemolysis and was found to be less than 15% for all the compounds when tested at highest concentration, i.e. 1200 μM. Interestingly, all the tested compounds inhibited Y–H transition in dimorphic C. albicans NCIM3557 at much lower concentration than their MIC90 values. Determination of ROS generation by diterpene 1 using DCFH-DA and DHR123 (dihydrorhodamine) staining of C. albicans NCIM3557 indicated production of intracellular ROS as a mechanism of antifungal activity.
Keywords: Diterpene; Polyalthia longifolia; Isolation; Flash chromatography; Natural products; Antifungal activity

Diastereoselective synthesis of beta-ether derivatives of artemisinin, an antimalarial drug: the effect of nitrile on stereoselectivity - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2016)
Malaria is a life-threatening disease affecting a major portion of the world's population with considerable loss of human life. Artemisinin, isolated from Artemisia annua, its oil- and water-soluble derivatives, and other known antimalarials are recommended for artemisinin combination therapy by the World Health Organization. We have established a method for the stereoselective synthesis of beta-ether derivatives of dihydroartemisinin in high yield and high diastereoselectivity. The reaction either in acetonitrile or dichloromethane/trichloroacetonitrile (6:1) mixtures at 0 degrees C or room temperature, respectively, furnished the antimalarial drugs artemether 3 or arteether 4 in high yield with a high diastereomeric ratio. The effect the nitrile has on the yield and stereoselectivity is mechanistically explained.
Keywords: antimalarials; arteethers; artemisinin; nitriles; trichloroacetimidates

Hemiketal-keto tautomerism in 2-deoxy-delta-lactones mediated by 2-lithiothiazole in solution state: a formal synthesis of DAH, Kamusol and their C-5 Epimers - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2019)
The reactions of 2-lithiothiazole on 3,4,6-tri-O-benzyl-2-deoxyglyconolactones have been studied, which resulted in the formation of two products, major (3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal) and minor products 3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal hemiketal. The hemiketal-keto tautomerism in solution was observed in the minor product. The tautomerism has been studied in various organic solvents and their ratios have been determined by H-1 NMR spectroscopy. The major product from the reaction of 2-lithiothiazole with 2-deoxygluconolactone was utilized for the synthesis of 3-deoxy-D-arabino-2-heptulosonic acid DAH 4 a and 3-deoxy-D-arabino-2-heptulopyranose commonly known natural product kamusol 6 a via acid catalyzed hydration followed by stereoselective methyl glycoside bond formation. Similarly, major product from 2-deoxygalactonolactone furnished 5-epi-DAH 4 b (C-5 epimer of 4 a) and 5-epi-kamusol 6 b (C-5 epimer of 6 a). The minor product has also been utilized for the synthesis of DAH 4 a, 5-epi-DAH 4 b, kamusol 6 a and 5-epi-kamusol 6 b through a common intermediate, alpha-methyl glycosylated product.
Keywords: hemiketals; Ketones; tautomerism; thiazoles; umpolung

Glycal mediated synthesis of piperidine alkaloids: fagomine, 4-epi-fagomine, 2-deoxynojirimycin, and an advanced intermediate, iminoglycal - Chand, Hemender R.; Tiwari, Mritunjay K.; Bhattacharya, Asish K. (RSC Advances, 2022)
Glucal and galactal are transformed into 2-deoxyglycolactams, which are important building blocks in the synthesis of biologically active piperidine alkaloids, fagomine and 4-epi-fagomine. In one of the strategies, reduction of 2-deoxyglycolactam-N-Boc carbonyl by lithium triethylborohydride (Super-Hydride (R)) has been exploited to generate lactamol whereas reduction followed by dehydration was utilized as the other strategy to functionalize the C-1-C-2 bond in the iminosugar substrate. The strategies provide the formal synthesis of 2-deoxynojirimycin, nojirimycin and nojirimycin B. DFT studies were carried out to determine the reason for the failure of the formation of the 2-deoxygalactonojirimycin derivative. Further, DFT studies suggest that phenyl moieties of protecting groups and lone pairs of oxygen in carbamate group plays a vital role in deciphering the conformational space of the reaction intermediates and transition-state structures through cation-pi or cation-lone pair interactions. The influence of these interactions is more pronounced at low temperature when the entropy factor is small.